A study from depression to recession to contraction - RK ARYA; WATTS, SWATI (International Journal of Psychosocial Rehabilitation, 2020)
The black swan event seen by way of the outbreak of the coronavirus has rattled all the economies. The countries have been affected to a varying degree but regaining the lost GDP and employment has to come with extra stimulus and each country might not be fully capable of overcoming the losses on account of employment and GDP. The advanced countries have learned to apply several other measures and their flexibility in taxation and adopting innovation quickly may take back them to normalcy early. But the developing countries who have limited head rooms and also the interest escalation is fast, the surging appears to be somewhat tardy. India is a victim of the large military of migrant workers most of which move from the low growth centers to high growth centers but the reversal means the same treatment to migrant workers who had faced the hardships when they were forced to move out of the cities. While decongestion is the demand of the ecosystem and there were immense opportunities as China who had churned for the last three decades but failing to deliver high growth must be easily accessed by India.